Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
The following values have no corresponding Zotero field: publisher: Gustav Fischer Verlag, Stuttgart
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a.; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals